STRATEGI KEPEMIMPINAN KEPALA SEKOLAH BERDASARKAN KECERDASAN EMOSIONAL DI SDN 2 GISTING PERMAI TAHUN AJARAN 2024-2025 - Anang Destian; Agus Sujarwo; Esen Pramudya Utama (UNISAN JURNAL, 2025)
The leadership strategy of the school principal based on emotional intelligence at SDN 2 Gisting Permai in the 2024-2025 academic year is crucial in creating a conducive school environment that supports the quality of education. This study used a qualitative method with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the principal has high emotional intelligence, reflected in the ability to manage their own emotions and those of others, as well as build harmonious relationships within the school environment. The principal also implements leadership strategies that encourage open communication, teacher empowerment, and effective conflict management. Providing emotional support to teachers and staff creates a positive work atmosphere, which in turn affects the quality of student learning. By prioritizing emotional intelligence in every aspect of leadership, the principal is able to create a school climate that supports teacher professional development and student well-being. This study provides an overview of the importance of emotional intelligence in school leadership to improve educational quality and relationships among school elements.